Pulmonary Resection for Metastatic Gastric Cancer - Kemp, Clinton D. (J Thorac Oncol, 2010)
INTRODUCTION: Sixteen percent of patients with gastric cancer will develop pulmonary metastases. Standard of care for these patients is systemic chemotherapy with a median survival of 6 months and a 5-year survival of only 2%. Our aim was to critically evaluate the published data on pulmonary resection for metastatic gastric cancer (MGC) and to analyze the potential rationale for surgical management to determine which patients may benefit from this approach. METHODS: The Pubmed and SCOPUS databases were queried for all studies reporting on pulmonary resections for MGC. All available clinicopathologic data were analyzed. RESULTS: Twenty-one studies from 1975 to 2008 reported 48 pulmonary resections in 43 patients including five repeat resections and four extrapulmonary metastasectomies. Eighty-two percent (34/43) of patients had solitary lesions with a median size of 24 mm (4–90 mm). Median time from gastrectomy to pulmonary resection was 35 months (0–120 months). At a median follow-up of 23 months, 15 of 43 (35%) patients were alive without disease, and two patients died without disease. Median survival was 29 months (3–84 months) after pulmonary metastasectomy and 65 months (5–180 months) after gastrectomy. Fifty-six percent (24/43) of patients had another recurrence at a median of 12 months (range: 6–48 months) after resection including 30% (13/43) of patients with pulmonary recurrences. Overall 5-year survival was 33%. CONCLUSIONS: Pulmonary metastasectomy for MGC can potentially result in long-term survival in a highly selected group of patients and should be considered for those who present with small, isolated lesions after a prolonged disease-free interval.